Azienda Ospedaliera "Carlo Poma", Mantova - Francesco Frattini; Silvia Crestani; Massimo Franchini (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
Data on the efficacy and tolerability of dasatinib in the treatment of chronic myeloid leukaemia (CML) derive from studies on extremely selected groups of patients, and so information from very elderly patients and patients with severe comorbid conditions are very scarce. This can lead to suboptimal or inappropriate therapeutic choices in such patients, with a significant impact on their quality of life and ease of management.